UNEMPLOYMENT. HUMAN CAPITAL. GENDER POLICY - G.Zh. Abdykerova; D.M. Aikupesheva (Academic Journal of Physical and Chemical Sciences, 2019)
In practice, there is a difference in life expectancy, literacy, education and earnings of men and women in the global trend in human development. At the same time, the possibilities of women are more limited than those of men. The unequal position of men and women entails negative socio-economic consequences: gender asymmetry in the labor market, the feminization of poverty, the problem of “double employment” of women. Gender-based discrimination also manifests itself in family decisions, unequal access to household incomes, unequal participation in raising children and family benefits, domestic violence, trafficking of women for the purpose of sexual exploitation, maternal mortality, short life expectancy men, low general health indices.